Propagator matrices as matrices of power's series. II. It's relationship with HF's stability problem and alternative solutions - Gómez, Carlos Anselmo (2003)
Some non-singlet quasi-instabilities (QIs) cases that arise in the calculation of NMR-Jparameters are analyzed within response theory. The relationship between ‘very close to zero’ eigenvalues of the principal propagator and the rate of convergency for specific coupling pathways is shown by a power series implemented to calculate the principal propagator matrix. A natural criterion for the analysis of the stability problem emerges from that series. This is more general and accurate compared with previous proposals. Its relationship with π-type molecular orbitals is given. We present an alternative scheme to minimize the effects of non-singlet QIs in such a way that the NMR-J parameters become close to the best theoretical calculations for H2CX (X=CH2, NH and O).